Fluorescence emission spectra of calcofluor stained yeast cell suspensions: heuristic assessment of basis spectra for their linear unmixing - Plášek, Jaromír; Dostál, Marek; Gášková, Dana (Journal of fluorescence, 2012)
Fluorescence emission spectra of yeast cell suspensions stained with calcofluor have recently been identified as promising markers of variations in the quality of yeast cell wall. It is shown in this paper how the raw fluorescence spectra of calcofluor can be transformed to reliable spectral signatures of cell wall quality, which are independent of actual dye-to-cell concentrations of examined cell suspensions. Moreover, the presented approach makes it possible to assess basis fluorescence spectra that allows for the spectral unmixing of raw fluorescence spectra in terms of respective fluorescence contributions of calcofluor solvated in the suspension medium and bound to yeast cell walls.
Keywords: Saccharomyces cerevisiae; Staining and Labeling; barvení a značení; suspenze; Benzenesulfonates; benzensulfonáty; vztah mezi dávkou a účinkem léčiva; Fluorescent Dyes; Dose-Response Relationship, Drug; Suspensions; Spectrometry, Fluorescence; glukosa; buněčná stěna; Glucose; Cell Wall; fluorescenční barviva; fluorescenční spektrometrie